PENGARUH FUMIGASI PHOSPINE (PH3) DALAM MENGENDALIKAN Tribolium castaneum (Herbst) PADA TEPUNG GANDUM - Ratna Sekar Arum; Saifuddin Hasjim (JURNAL BIOINDUSTRI (JOURNAL OF BIOINDUSTRY), 2020)
Tribolium castaneum is primary pest in flour commodities and becomes a secondary pest in rice dan cereals. The damage caused by this pest attack is in the form of decreasing the quality and quantity of flour. One of the measure control of T. castaneum is fumigation using fosfin (PH3). This study aims to determine the percentage of mortality and find out the percentage of pupae become imago to the treatment of various doses and fumigation duration. The methode used is Completely Randomized Design (CRD) with 12 treatments and, 1 control and 3 replications. The variables observed included the mortality of larvae and imago, the number of pupae which turn into imago as well. The results of the observed variables were analyzed using variance and using the DMRT follow-up test with a level of 5%. The results of this study indicate that the use of phosphine fumigation is effective for controlling the pest of T. castaneum. The effective dose for controlling T. castaneum in this study was at a dose of 1g /m3 with a 12-hour exposure period and reduce the percentage of pupae which turn into imago by 0%.